(untitled) (Journal of Information Technology and Digital World, 2021)
There is a need for better medical and preclinical instruments to diagnose knee OA in its initial phases owing to the increase occurrence of knee osteoarthritis (OA), a devastating knee joint degeneration. Osteoarthritis commonly affects patients who are obese and those above the age of 60. This mainly happens to age down and over-weighted people. The goal is to provide practical methods for assessing the seriousness of knee OA quickly and with human consistency. We also present Changes that affect your chances of getting sick of knee osteoarthritis, Treatment of knee osteoarthritis and the Prevention methods of knee osteoarthritis.